Hybrids between cork oak and holm oak: Isoenzyme analysis - Oliveira, Paulo (2007)
Hybrids between cork oak and holm oak occur in a large range of overlap between these two species in Portugal, and the subsequent crosspollination involving the hybrids and cork oak has been postulated to result in some of the worst cork-producing trees in Portugal. A methodological framework was set for the routine large scale detection of hybrid genotypes using isoenzyme analysis. The effectiveness of isoenzyme markers enabling the discrimination of the hybrid trees from both parent species was probed on the nursery-grown progenies derived from reference “pure” populations, selected mixed stands and hybrid individuals. No spontaneous hybrid was detected among 1141 seedlings originating in the mixed stands, thus suggesting that the incidence of hybridization is quite low. The seedlings derived from 3 hybrids confirmed that the discriminant isoenzyme loci recombined and segregated the parental types, and a strong preference for mating with cork oak in two of these hybrids was suggested. A substantial increase of the fixation index F within a single generation for the polymorphic cork oak phosphoglucose isomerase locus may indicate that a significant proportion of seedlings derive from short-range pollen, a factor that might weigh on the formation of hybrids between these two species.